Mengembangkan Potensi Pelajar Yang Aktif, Cerdas dan Mandiri Dengan Cara Menabung - Ni Ketut Sriwinarti; Khairunnisa Khairunnisa; Defel Septian; R. Ayu Ida Aryani (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service activity aims to train young children to be more independent, especially in realizing their desire to have something in the future. Children are invited to learn to manage personal money, have financial planning, respect money, learn discipline and make them proud. One of the simplest saving methods is to save money through a medium called a “celengan”. This service activity was carried out at Guntur Macan 1 State Elementary School, where the participants in this activity were student in grades 4 and 5. The method of implementing this socialization was divided into several stages, namely coordination, media preparation, material socialization, discussions and games. The socializations material provided is history of saving, why you save, what banks are in Indonesia, and finally setting a savings target. The material is packaged with interactive videos so that children can be enthusiastic in participating in all the activities. This activity went well and was lively because it was accompanied by college students who guided the activity will provide ongoing motivation for children to continue saving an so that the agreed targets can be achieved